EVOLUTION OF COMET-LIKE ORBITS OF METEORITE- PRODUCING GROUPS AND THEIR PARENT BODIES - Konovalova, N. A.; Gorbanev, Yu. M.; Davruqov, N. H. (Одеські астрономічні публікації, 2019)
This paper presents the results of the study of evolution of Jupiter-family comet-like orbits of six meteorite-producing groups, including sporadic fireballs from the IAU MDC database 2007 [1], sporadic meteors from the SonataCo database [2], instrumentally observed H5 and L3.5 ordinary chondrites, as well as near-Earth asteroids which are potential parents of the examined groups. In order to verify the relationship between meteorite-producing groups and their potential parents, we performed backward numerical integration of the orbital motion of these groups’ members over several millennia. The numerical integration was carried out using the Halley software [3]. The equations of motion factored in gravitational perturbations due to the major planets, radiation pressure effects and the Poynting-Robertson drag. The equations of motion were numerically integrated using the 11 th -order Everhart method applicable to studying the motion of Jupiter-approaching short-period comets. The numerical integration of the mean orbital elements of a group, as well as those of the relevant meteorite and potential parent asteroid, over 5,000 years has shown that the respective perihelia, eccentricities and arguments of perihelion evolved in a similar manner over the specified period. The D SH -criterion of Southworth and Hawkins [4], which is a quantitative measure of orbital similarity, has remained below 0.3 [5] for about 5,000 years in the groups of Neuschwanstein and Mason Gully meteorites and for about 3,500 to 4,500 years in the groups of Benešov and Park Forest meteorites. In the groups of the Košice and Pribram meteorites, the mean orbits and those of their potential parents remained similar as defined in terms of the D SH -criterion over a relatively short period of about 2,000 to 3,000 years. We can infer from our findings that meteorite-producing sporadic fireballs and sporadic meteors are related to the H5 and L3.5 ordinary chondrites and their potential parents, i.e. near-Earth asteroids, in the investigated groups. The estimated time intervals, over which the evolving orbits of the groups’ members have shown good similarity, are indicative of relatively recent formation of meteorite-producing groups as a result of fragmentation of their parent bodies.